Economic Community of West African States (Ecowas) and State Sovereignty in West Africa - Ikponmwosa, Mercy Ehidiamen; Omodia, Stephen. M.; Efanodor-Obeten, Harriet Omokiniovo (Indonesian Journal of Political Studies, 2024)
States are now recognizing the need to take action to create and improve regional institutions in virtually every region of the world, including Africa, and integration even in West Africa has become fashionable over the years. ECOWAS revised treaty seek to promote supranational tendencies giving room for state reluctance in the implementation of its policies and decision. With the Economic Community of West African States (ECOWAS) as its focal point, the study looks at the integration process in West Africa as well as how it affects state sovereignty in the subregion. Secondary data sources, namely journals and publications, are used in the study. The study finds among other things that ECOWAS uses the needs, policies and activities of state to interfere in the affairs of member states thereby limiting her sovereignty to an extent within the region. The study concludes that with national interest at heart, states knowing both the cost and benefits of integration will usually strive to accomplish their aims and objectives. It recommends that policies and initiatives should be developed to support both state autonomy and regional collaboration to aid development, stability, and economic growth among states and to also encourage both local and foreign investors, contributing to the overall development of the states in the West African Region.